Indonesia’s UNIFIL Dilemma: Balancing Strategic Autonomy and Peacekeeping Risks after the 2026 Casualties - Maria Anatasya Sekar Pamungkas; Fauzia Gustarina Cempaka Timur; Rodon Pedrason (Darul Yasin Al Sys, 2026)
Although Indonesia’s participation in United Nations peacekeeping operations has received considerable scholarly attention, research specifically addressing the intersection of defense diplomacy, strategic autonomy, and rising peacekeeping risks within the United Nations Interim Force in Lebanon (UNIFIL) remains limited. This study aimed to analyze how Indonesia balances its defense diplomacy objectives and strategic autonomy amid escalating operational risks affecting peacekeeping personnel in southern Lebanon. A qualitative approach with a descriptive-analytical case study design was employed, relying on purposively selected documentary sources relevant to Indonesia’s participation in UNIFIL. Data were collected through document analysis of United Nations reports, UNIFIL publications, Indonesian government documents, policy statements, academic literature, and reputable international media sources. The data were analyzed using qualitative thematic analysis through data reduction, categorization, interpretation, and synthesis of recurring themes. The findings indicate that deteriorating security conditions in southern Lebanon have significantly transformed the operational environment of peacekeeping missions, increasing personnel vulnerability and operational unpredictability for troop-contributing countries, including Indonesia. Despite these growing risks, Indonesia has maintained its participation in UNIFIL while strengthening institutional preparedness, diplomatic engagement, and force protection considerations. The findings further suggest that Indonesia’s continued participation reflects a strategic balancing process between maintaining international legitimacy and responding to domestic accountability concerning personnel safety. This study contributes to defense diplomacy and strategic autonomy literature by demonstrating that peacekeeping participation increasingly requires institutional adaptation under volatile and high-risk operational conditions. The study concludes that stronger institutional preparedness and multilateral coordination are essential to sustaining Indonesia’s peacekeeping commitments in increasingly unstable conflict environments. Its implications include theoretical contributions to peacekeeping and defense diplomacy scholarship and practical relevance for policymakers in strengthening deployment preparedness and peacekeeper protection mechanisms.